The Virulence of a Dickeya dadantii 3937 Mutant Devoid of Osmoregulated Periplasmic Glucans Is Restored by Inactivation of the RcsCD-RcsB Phosphorelay - Bouchart, Franck (American Society for Microbiology (ASM), 2010)
Dickeya dadantii is a pectinolytic phytopathogen enterobacterium that causes soft rot disease on a wide range of plant species. The virulence of D. dadantii involves several factors, including the osmoregulated periplasmic glucans (OPGs) that are general constituents of the envelope of proteobacteria. In addition to the loss of virulence, opg-negative mutants display a pleiotropic phenotype, including decreased motility and increased exopolysaccharide synthesis. A nitrosoguanidine-induced mutagenesis was performed on the opgG strain, and restoration of motility was used as a screen. The phenotype of the opg mutant echoes that of the Rcs system: high level activation of the RcsCD-RcsB phosphorelay is needed to activate exopolysaccharide synthesis and to repress motility, while low level activation is required for virulence in enterobacteria. Here, we show that mutations in the RcsCDB phosphorelay system restored virulence and motility in a D. dadantii opg-negative strain, indicating a relationship between the Rcs phosphorelay and OPGs.